Capability Assessment Model Development Micro Teaching Music Education Students Jurusan Sendratasik FBS UNP - Esy Maestro; Ambiyar Ambiyar; Ishak Aziz (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2021)
This article is written based on research to produce a model and assessment system of teachingpracticeability, which can be utilized  Educators and Education. This research was conducted by considering the need: (1)     development of teaching practice skills that can improve students' high-level thinkingability, (2) assessment models relevant to learning achievements, (3) implementation of various and  feasible assessments for students, as well as (4) the application of learning achievement assessment models and systems taking into account a variety of interests and talents. Data is collected through expert evaluation of teaching ability formulation and teaching ability assessment model and through focus group discussion with staff who are interested in the implementation of assessment. Data/information analysis is done descriptive qualitatively and quantitatively in accordance with the type of data collected. The results stated that the hypothetical model for assessment of teaching practice  skills     of music education students who demanded theavailabilityof: (1) practical classes and practical exams and labor praktik; (2) mentoring/instructors, examiners, and IT staff with sufficient amount and quality; and (3) guidelines and procedures as a reference for all parties involved in the implementation of the assessment.